Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/fsn3.3197
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and dietary acid load in relation to cardiovascular disease mortality: Results from Fasa PERSIAN cohort study

Abstract: Background: Dietary intake is a determining factor in the morbidity and the mortality of chronic disorders. However, not many documents have investigated this relationship. The aim of this study was to evaluate the associations of the Dietary In ammatory Index (DII), Alternative healthy eating index (AHEI), Mediterranean dietary score (MDS), DASH score, and dietary acid load with cardiovascular disease (CVD) mortality.Method: 2158 CVD patients (mean age of 54.73 ± 8.62 years) from the Fasa Cohort Study, Iran p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Preserving skeletal muscle could improve survival in patients with cirrhosis 63 , 64 . Finally, it is important to note that 40% of the deaths in this study were due to CVD, which has previously been shown to be associated with DAL, and some similar mechanisms have been proposed to explain its association 34 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Preserving skeletal muscle could improve survival in patients with cirrhosis 63 , 64 . Finally, it is important to note that 40% of the deaths in this study were due to CVD, which has previously been shown to be associated with DAL, and some similar mechanisms have been proposed to explain its association 34 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, Xu et al 37 found that both excess acid and alkali load in the diet may be associated with an increased mortality risk, especially CVD-caused mortality, among Swedish adults (a U-shaped association). Furthermore, the recent study conducted by Fereidouni et al 34 indicated that an increase in dietary acid load may lead to an increased risk of CVD-related mortality. Aside from that, several studies have suggested that DAL may be associated with non-alcoholic fatty liver disease (NAFLD) progression 38 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Not only metabolic acidosis but also a high DAL has been associated with increased (cardiovascular) morbidity and mortality in multiple observational cohorts [ 2 , 6 , 38 , 130 ].…”
Section: Dietary Acid Load In Metabolic Disordersmentioning
confidence: 99%
“…Fereidouni et al evaluated multiple dietary scores (Mediterranean dietary score, Alternative Healthy Eating Index score, DASH score, Dietary Inflammatory Index score, and dietary acid load) with regard to mortality risk in 2158 cardiovascular disease (CVD) patients. The authors concluded, based on a limited 3-year follow-up, that only the Dietary Inflammatory Index score (HR 1.11; 95% CI 1.01–1.24 and dietary acid load (HR 1.02; 95% CI 1.01–1.03) were significantly associated with increased mortality in CVD patients [ 38 ]).…”
Section: Dietary Acid Load In Metabolic Disordersmentioning
confidence: 99%
“…The potential mechanisms may include elevated inflammation and oxidative stress levels, deficiencies in essential nutrients, and irregular meal times [ 2 ]. On the other hand, a high-quality dietary pattern characterized by low inflammation, low sugar, and high dietary fiber can lower the incidence of cardiovascular diseases and cancer, thereby reducing long-term mortality rates [ 3 , 4 ]. The Mediterranean diet (MED) is characterized as rich in fruits, vegetables, whole grains, nuts, legumes and fish, as well as healthy unsaturated fatty acids, vitamins and trace elements [ 5 , 6 ] MED has been widely recognized as beneficial to the cardiovascular system, reducing the risk of long-term cardiovascular disease (CVD)[ 7 ].…”
Section: Introductionmentioning
confidence: 99%